(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The secondary entry portal of the Indonesian Throughflow (ITF) from the Pacific to Indian Oceans is considered to be via the Halmahera Sea (HS). However, few ITF studies have been done within the passage. This motivated the Internal Tides and Mixing in the Indonesian Througflow (INDOMIX) program to conduct direct measurements of currents and its variability across the eastern path of the ITF. This study focused on the intra-seasonal variability of near-bottom current in HS (129°E, 0°S), its origin and correlation with surface zonal winds and sea surface height over the equatorial Pacific Ocean. The result showed a strong northwestward mean flow with velocity exceeding 40 cm/s, which represented the current-following topography with the northwest orientation. Meridional current component was much stronger than the zonal component. The energy of power spectral density (PSD) of the current peaked on 14-days and 27-days periods. The first period was presumably related to the tidal oscillation, but the latter may be associated with surface winds perturbation. Furthermore, cross-PSD revealed a significant coherency between the observed currents and the surface zonal winds in the central equatorial Pacific zonal winds (180°E-160°W), which corroborates westward propagation of intra-seasonal sea surface height signals along the 5°S with its mean phase speeds of 50 cm/s, depicting the low-latitude westward Rossby waves on intra-seasonal band. Keywords: current, equatorial Pacific Ocean, zonal winds, sea surface height, Halmahera Sea